Rastros de escrituras : periódicos científicos da área da educação na região Centro-Oeste brasileira e o nexo com os critérios heterônomos Qualis - Trindade, Dionéia da Silva (2022)
This doctorate research presents a study on the online open access-scientific journals of the Education area of study in the Brazilian midwest region and the nexus with the heteronomous criteria of the Qualis System. It is a research, encompassing the Humanities area, highlighted by the Education field focusing on the Stricto Sensu Post-Graduation, having its boundaries with the Philosophy of Difference. It aims at composing a cartography of scientific journals in the field of Education and the Qualis Systems strata, concerning the year periods of 2013-2016 and 2017-2018. The analytics were based on Jacques Derrida's concept of writing, as well as, the specific literature on the subject of the study. The question which brought out the analytical trajectory was: which normative acts validate and qualify a scientific journal in Brazil? The method of the study counted on the cartography as thought by Gilles Deleuze and Félix Guattari. They conceived the attribution of a method as aimed at following a process. Cartography, attributed as a method, creates its own movements, its deviations and reinvents them. Based on that, the exploratory research, document analysis and the reading of letters and editorials of five scientific periodicals were in this study used, taking as a selective criterion to those related to the Forum of Periodical Editors in the Area of Education (FEPAE) - organization of the Association of the National Researchers in Education (ANPEd) -, in the midwest region, and qualified by the Coordination for the Improvement of Higher Education Personnel (CAPES), with the Qualis A2 stratum, in the 2013-2016 quadrennial, namely: History of Education Journals; Education and Philosophy; Journal of Public Education; Brazilian Journal of Pedagogical Studies; Brazilian Journal of Education Policy and Administration. Firstly, the cartography searched for scientific articles on the electronic portals: Google Scholar, SciELO Brazil platform and CAPES Periodicals portal. It was used the descriptors: scientific journals and education; Qualis periodicals + education. Subsequently, it was done a survey in the Documents of the Area 38: Education on the CAPES Sucupira platform, accessible on the internet. The bibliographical intersections followed a cartographic map, encompassing the discussion on the Qualis journals, in which three major areas of knowledge were revealed: Human Sciences, Applied Social Sciences and Health Sciences, and their respective sub-areas. The publications present confluent points encompassing aspects of evaluation and the stream of intellectual production of the post-graduation programs (PPG), specifically in the area of Education. The document analysis pointed to a compound of evaluation criteria and parameters with different weights in the two analyzed periods, from A1 to B5 and C; and A1 to B4 and C. In the unfolding of the analytics of the letters and editorials, the multiplicities that emerged from the ordinary life and the discourses that differ from each other and also in themselves. The informational streams arising from the letters revealed scriptures which end up claiming that scientific journals affect the traditional philosophical glossary and invent means to deterritorialize their own stories. And the proper names, in the announced letters, were not destroyers of deterministic laws, they brought in their writings the critical reterritorialization of the discourse in the possibility of intervening in the reproduction of the heritage that modernity has projected on us. In this sense, it is understood that language involves the need for its own criticism and, in this idea, the male author and the female author throughout his/her makings proposes a critique of the value of the criterion of truth.